Identification of Docetaxel as a Potential Drug to Promote HDL Biogenesis - Choi, Hong Y.; Ruel, Isabelle; Genest, Jacques (Frontiers in Pharmacology, 2021)
Objective: Our recent studies showed that desmocollin 1 (DSC1) binds to apoA-I in order to inhibit apoA-I-mediated high density lipoprotein (HDL) biogenesis in atherosclerotic plaques. To promote HDL biogenesis in the plaque, here we search for small molecules that block apoA-I-DSC1 interactions. Approach and Results: We combined mutational and computational mapping methods to show that amino acid residues 442-539 in the mature DSC1 protein form an apoA-I binding site (AIBS). Using a crystal structure of the AIBS, we carried out virtual screening of 10 million small molecules to estimate their binding affinities to the AIBS, followed by the selection of 51 high-affinity binding molecules as potential inhibitors of apoA-I-DSC1 interactions. Among the 51, the chemotherapy drug docetaxel showed the highest potency in promoting apoA-I-mediated HDL biogenesis in primary human skin fibroblasts with the half-maximal effective concentration of 0.72 nM. In silico docking studies suggest that the taxane ring in docetaxel binds to the AIBS and that the carbon-13 sidechain of the taxane tightens/stabilizes the binding. The HDL biogenic effect of docetaxel was also observed in two predominant cell types in atherosclerosis, macrophages and smooth muscle cells. Importantly, docetaxel promoted HDL biogenesis at concentrations much lower than those required for inducing cytotoxicity. Conclusions: Determination of the AIBS in DSC1 and AIBS structure-based virtual screening allowed us to identify docetaxel as a strong HDL biogenic agent. With the remarkable potency in promoting HDL biogenesis, a chemotherapy drug docetaxel may be repurposed to enhance atheroprotective HDL functions.